Post-Agricultural Shifts in Soils of Subarctic Environment on the Example of Plaggic Podzols Chronosequence - Timur Nizamutdinov; Sizhong Yang; Evgeny Abakumov (Agronomy, 2025)
This study investigates the post-agricultural transformation of Plaggic Podzols in a Subarctic environment, focusing on the Yamal region, Western Siberia. Agricultural practices historically altered the natural Histic Entic Podzols, leading to their conversion into anthropogenic soils with enhanced organic matter and nutrient profiles. Using a chronosequence approach, soil profiles were analyzed across active and abandoned agricultural fields to assess changes in soil properties over 25 years of abandonment. Results revealed a significant decline in SOC (2.73 → 2.21%, r2 = 0.28) and clay (5.26 → 12.45%, r2 = 0.84), which is reflected in the values of SOC/clay and SOC/(silt + clay) ratios. Nevertheless, the values of the ratios are still above the thresholds, indicating that the “health” of the soils is satisfactory. We detected a decrease in Nt (0.17 → 0.12%, r2 = 0.79) and consequently an increase in the C:N ratio (18.6 → 22.1), indirectly indicating a decrease in SOM quality. Nutrient losses (NPK) with increasing abandonment periods were pronounced, with their concentrations indicative of soil quality degradation. Trace metal concentrations remained below pollution thresholds, reflecting minimal ecological risk according to Igeo, RI, and PLI indexes. The results highlight the necessity for further research on organo-mineral interactions and SOM quality assessment. The findings provide insights into the challenges of soil restoration in Polar regions, emphasizing the role of climate, land-use history, and management practices in shaping soil health and fertility.